Chronotypes in middle‐aged women with polycystic ovary syndrome: A population‐based study - Linnea Kroneld; Päivi Polo‐Kantola; Meri‐Maija Ollila; Riikka K. Arffman; Elisa Hurskainen; Laure Morin‐Papunen; Varpu Jokimaa; Terhi T. Piltonen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Circadian rhythm disruption has been associated with the risk of polycystic ovary syndrome (PCOS), as the evening chronotype (EC) shares several traits with PCOS, including metabolic disorders, cardiovascular diseases, and psychiatric disorders. It has been suggested that the biological clock could be targeted with new, preventive, and therapeutic strategies for PCOS in women with biorhythm disorders. We evaluated inner circadian rhythmicity in middle‐aged women with PCOS in a population‐based setting, focusing on whether women with PCOS and an EC have a specific subtype in relation to their clinical characteristics. Material and Methods The data derived from the Northern Finland Birth Cohort, a population‐based longitudinal birth cohort of 12 058 individuals born in 1966. We compared the circadian phenotype between 314 women with PCOS (according to the Rotterdam criteria) and 1248 women without PCOS at age 46 years using the validated Finnish shortened 6‐item Morningness‐Eveningness Questionnaire (sMEQ) and the single‐item self‐assessed morningness‐eveningness question. Results PCOS was not associated with the EC by the sMEQ (p = 0.495) or self‐assessment (p = 0.303). The self‐assessed morningness‐eveningness values differed from the sMEQ chronotype distribution (p < 0.001), nevertheless, the most frequent chronotype was the intermediate chronotype (IC) determined by both chronotyping methods (sMEQ PCOS 47.7% vs. 45.2% non‐PCOS; self‐assessment PCOS 66.5% vs. 68.4% non‐PCOS). The hyperandrogenic PCOS phenotypes A–C did not differ from the non‐hyperandrogenic phenotype D as for the chronotype (p = 0.271). The EC was associated in both groups with depressive and anxiety symptoms (PCOS p = 0.012, non‐PCOS p < 0.001) and the use of sleep medication (PCOS p = 0.017, non‐PCOS p < 0.001). Conclusions The EC was not over‐represented in middle‐aged women with PCOS or in the hyperandrogenic PCOS phenotypes A–C in our study. This does not support the need for chronotyping in the comprehensive assessment of women with PCOS. However, as chronotypes tend to change with aging, cross‐sectional studies in different age groups are warranted to draw conclusions on the role of chronotypes in PCOS and the associated metabolic risks.